SEMANTIC GROUPS OF PREDICATIVE ADVERBSIN THE WORKS OF ALEXANDER DOVZHENKO - Tetiana V. Melkumova; Viktoriia M. Zinchenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article analyzes the semantic groups of predicative adverbs in the works of O. Dovzhenko. Due to the peculiar morphological categories, adverbs attract the attention of scientists around the world. The subject of intelligence is the classification of adverbs, contacting adverbs and verbs in a sentence, studying adverbs when mastering different languages and even understanding the shades of meanings of adverbs-synonyms. The idiosyncrasies of different artists are always of interest to a wide range of linguists and art critics. The language of O. Dovzhenko’s creative heritage has been analyzed by authoritative scientists. The relevance of our work is due to its focus on the study of the semantic aspect of predicative adverbs in the literary heritage of O. Dovzhenko, whose creative work is respected in world culture. The purpose of the research is to analyze the semantic groups of predicative adverbs in Dovzhenko’s works of art. The object of research is predicative adverbs in the works of O. Dovzhenko. The subject of research is the semantic aspect of the functioning of predicative adverbs in the works of O. Dovzhenko. Quantitative analysis of the use of predicative adverbs in Dovzhenko’s works has revealed a significant use of words to describe the state with a modal tone, words to denote the physical, mental, intellectual and emotional state of man and moderate use of words to denote the environment surrounding the characters. Predicative adverbs of different semantic groups are found in Dovzhenko’s works. In the group of words to define the state with a modal tinge there are predicative adverbs that reflect the visual sensations of the characters, convey emotional assessment to the content of transmitted information (mostly difficult moods), serve to establish optimal verbal contact with the listener, express the appeal to the interlocutor, indicate the obligation/non-obligation of certain actions, the possibility of performing certain actions, the time limit on the duration of certain actions. The group of words to denote the physical, mental, intellectual, emotional state of man and creatures in general include predicative adverbs that express negative emotions of characters (sadness, heaviness, annoyance, etc.), characterize the physical condition of characters, denote positive mental and emotional states of persons. The semantic group of predicative adverbs to denote the state of the environment surrounding the characters of the work includes predicative adverbs that activate the auditory and visual sensations of readers, reflect feelings of non-beings, denote positive phenomena in the environment surrounding the characters. The research is promising in the direction of elucidating the pragmatic function of predicative adverbs in the works of O. Dovzhenko in order to enrich information about the creative skills of the outstanding artist.